Briefing with artificial intelligence for requirement elicitation: Three cases with ChatGPT for exploration of possibilities - Çalışkan, Ekrem Bahadır (Wywiad ze sztuczną inteligencją w procesie zbierania danych do projektowania: Badanie możliwości ChatGPT – trzy przypadki, 2023)
Architectural program is important knowledge of space requirements affecting the design besides context, concept, and intentions. The requirement knowledge is elicited and validated between project stakeholders during the pre-design and design process. The complexity of defining requirements and the difficulty capturing knowledge from project parties vary. Briefing is a vital process to capture, refine, create, and manage space requirements from end-users. Lacks of communication, the inclusion of user clients, and clarity of objectives are critical for eliciting requirements. The AI tools offer many possibilities to diverse areas, and several studies have been conducted recently. The research seeks the usage of AI to capture the building requirement by putting it in the position of the end-user. For this purpose, ChatGPT was used, a language model capable of generating texts and predicting and creating knowledge. The study’s objective is to explore AI’s limits and capabilities for the briefing process to initiate the requirement elicitation. Within the semi-structured interview process, the briefing session was executed for three cases by putting the AI in the end user position. The results are promising in the requirement elicitation of pre-project stages considering the clarity of the architectural program, integrity in context, and usage of time. The argued contribution of AI in architectural projects requires further research; however, the study underlines the possible usage of AI for defining the requirements of the spaces. The avenues of further research may include validating captured knowledge processes needed, examining the AI for different building typologies and project stakeholders, and seeking the bias, ethical concerns, and combinations of humans and AI for various tasks.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 93-101
Keywords: architektura; artificial intelligence; briefing; requirement capturing; ChatGPT; end-user; sztuczna inteligencja; wywiad; uchwycenie wymagań; użytkownik